The Impact of Relationship Marketing and Service Quality on Satisfaction and Its Impact on Patient Loyalty at Hospital: Case Study of a Hospital in Garut Regency - Panji Gani Nugraha (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
Based on information from the West Java Health Office, there are six hospitals serving patients. However, there are problems due to the dissatisfaction felt by patients so the value of unmet need services in West Java from the last three years has decreased. The purpose of this study was to determine the effect of relational marketing and service quality on satisfaction and its impact on customer loyalty in hospitals. The scope of this research is six hospitals located in Garut Regency. This study uses descriptive and associative analysis methods of causal relationships. The type of this research is quantitative. Respondents in this study were 100 respondents using purposive sampling techniques and unknown populations. The data collection technique uses the distribution of questionnaires with a Google form.Â The data analysis method used is validity, and reliability and uses a series of analysis path tests using SEM-PLS. The results showed that all variables can be said to be affected. This study concludes that relational marketing and service quality affect customer satisfaction and customer loyalty.